Analisis Daya Dukung Lahan Sawah di Kelurahan Sedau Kecamatan Singkawang Selatan Kota Singkawang - Rahman, Muhammad A; Riduansyah, Riduansyah; Krisnohadi, Ari (Fakultas Pertanian Universitas Tanjungpura, 2023)
Paddy production at Sedau Village are improving caused by land characteristics. Then the carrying capacity would be counted by it correlation between the amount population and paddy productivity each year. The object of the research are to identify soil characteristics, determine cluster type and the carrying capacity of rice fileds in Sedau Village. The research method is soil survey, soil sample analysis, multivariate regression analysis, cluster analysis and the analysis of the carrying capacity. The results showed, variables affecting rice production were Bulk Density, Permeability, P-available and K-exchangeable. If Soil Bulk Density and Permeability are increased, so the paddy production will decrease. If P-available and K-exchangeable are increasing, so the paddy production will increas too. Following the formula: Y=1.605